(untitled) (Indian Journal of Child Health, 2019)
Background: High morbidity and mortality of swine flu in children result in frequent hospitalization. Clinical and laboratory parameters predicting the duration of hospitalization are important but not studied in children till date. Aim: This study aims to evaluate the clinical and laboratory predictors of hospitalization (>7 days) and clinicodemographics in children with swine flu infection. Materials and Methods: This retrospective study was done in the department of pediatrics of a tertiary care center in Delhi. The records of children between the age group of 1 and 14 years of age in the previous 3 years and having clinical symptoms and real-time polymerase chain reaction positive for H1N1 infection were included in the study. Baseline characteristics, clinical details, laboratory profile, and treatment of these patients were recorded and analyzed. The outcome parameters were compared between Group A (children hospitalized for ?7 days) and Group B (hospitalized for >7 days) by appropriate statistical analysis. Results: Of 51 children analyzed, the mean age was 45.83 months and three-fourth of them were ?5 years (50% of infants). The mean duration of hospitalization in Group A and Group B was 5.09±1.82 and 11.2±4.51 days, respectively. Patients with longer duration of breathlessness (mean difference 1.75 days, p=0.026), hypoxemia, cyanosis, and neutrophil/lymphocyte (N/L) ratio <2 after 48 h of admission were associated with prolonged hospitalization (p<0.05). Mean temperature at admission, absolute neutrophil counts, absolute lymphocyte counts, C-reactive protein levels, arterial blood gases parameters, or percentage of children with fever, altered sensorium, respiratory distress, anemia, leukocytosis, and N/L<2 at admission were comparable between the two groups (p>0.05). The most common presenting symptoms were fever (98%), cough (98%), rhinorrhea (88%), and breathing difficulty (88%) with asthma as the most common comorbid factor. Conclusion: The swine flu is a mild illness with highest hospitalization in children <5 years with non-specific clinical and laboratory features. Breathlessness of longer duration, hypoxemia, cyanosis, and N/L ratio <2 after 48 h of admission were risk factors for hospitalization of more 7 days.